S’affirmer en tant qu’homme par la lutte : le genre comme outil politique pour les travailleurs maghrébins dans les années 1970 ? - Baptiste Feuillye (Genre & Histoire)
This article questions the popular orientalist belief that eroticizes the figure of the “Arab man” and its influence on the Maghrebin workers mobilizations in the 1970’s. It focuses on the particular case of a hunger strike by undocumented workers from Tunisia that took place in March 1973 in Vaise, a neighbourhood of Lyon. This social conflict was part of the protest movement against the Marcellin-Fontanet circulars in France, and more generally in an unprecedented period of mobilization of postcolonial immigrant workers in the early 1970s. This paper first addresses by which processes these Maghrebin workers were gendered and assigned to a marginal masculinity within French society. This allows us to see the centrality of gender issues within these conflicts, used as a tool used by hunger strikers to empower themselves as legitimate political subjects. Finally, the article examines the ambivalences of the hunger strike as a mode of action, and how it affects the relationship between activism and masculinities. Throughout this reflection, the role of the space of mobilization in the dynamic transformation of the masculine identities of these workers –and more generally of gender relations – will gradually become apparent.